Stress factors and cytotoxic and genotoxic action of ethanol in Saccharomyces cerevisiae - Mascarenhas, Maria do Socorro (2024)
In industrial fermentation, Saccharomyces cerevisiae are exposed to different stress conditions. In this sense, the aim of this study was to evaluate the toxic action of ethanolic stress on Saccharomyces cerevisiae. Exploratory research was carried out on the stress factors that cause injuries in yeast. Fermentation tests were conducted with the Fleischmann® and Pedra-2 strains, cultivated in sugarcane juice at 22 ºBrix and pH 5.0, adding concentrations of 5, 10, and 15% of ethyl alcohol, and incubated at 30°C at 250 rpm for 10 hours. For the cytotoxic tests, 100 µl of samples were collected for evaluation of cell growth by spectrophotometric measurements at 570 nm, and 5 µl were dripped into Petri dishes containing 2% YPD solid medium and incubated at 30ºC for 72 hours for colony growth. For the genotoxicity test, the comet test was used with 0.5 µl of the samples added to slides previously prepared and subjected to electrophoretic running and subsequently stained in a 0.1% silver nitrate solution. 100 random nucleotides were evaluated, evaluating five DNA damage classes (0, 1, 2, 3, and 4) according to the intensity and pattern of genetic material entrainment. The results show that stress factors interfere with yeast performance. Fleischmann® showed sensitivity to ethanolic stress.